Spiritual Decline as a Predictor of Posttraumatic Stress - Crete, Abigail (Religions, 2020)
Many college students in the United States arrive on campus with exposure to both traumatic events and typical negative life events, as well as varying levels of emotional wellness. One way that students may seek out help is through spiritually supportive wellness programming. The current study examines the prevalence of and relationship between traumatic life events, typical negative life events, and spiritual growth and decline as predictors of posttraumatic stress in a sample of undergraduates (N = 88) seeking spiritually supportive wellness. Traumatic and typical negative life events and spiritual decline were predictive of posttraumatic stress. Furthermore, a moderation effect was found such that while participants with high trauma exposure and high spiritual decline reported the highest posttraumatic stress, those with high trauma exposure and low spiritual decline reported lower posttraumatic stress, similar to those with low trauma exposure. These results have implications for the role of spiritual decline in the etiology of PTSD (Posttraumatic Stress Disorder) within emerging adult populations who identify as spiritual that warrant further study.